Legal and Economic Dimensions of the Corona Virus - Saeed, Bakhshan R. (Mitanni Journal of Humanitarian Sciences, 2021)
The international crisis represented by the emergence of the "Corona virus" has caused several economic and political disturbances at the international level, and before talking about its dimensions, we make it clear that the Corona virus is embodied in a virus with a size of 0.85 autogram, and it is one of the strains of the SARS virus (severe acute respiratory syndrome) that appeared in 2002 / 2003, and the Corona virus threatens nearly 7 billion people in the world, as it has various effects in all developmental areas in society, such as the health field, as well as the industrial, agricultural and commercial fields, the education sector, and tourism, and thus affecting the national economy, and economic development, and that At the domestic and international levels, this disease, by appearing in a seafood market in the Chinese city of Wuhan, has turned into an “outbreak” stage, It is the sharp increase in spread in an area or a relatively limited population, then it reached the stage of “epidemic”, meaning the sharp increase that covers a larger area or a larger number of people within one continent, and soon turned into a “pandemic”, which is the sharp increase in The disease that strikes several different countries on several continents, therefore, the Corona virus represents a global crisis that has led to international economic and political turmoil, due to its geographical and substantive scope without borders, as its effects exceeded regional borders, which requires the rise of all countries and their solidarity internationally, politically and economically to confront this crisis. Therefore, research asks about the economic effects of the Corona virus crisis on countries, in terms of their political and economic relations with each other? And the dimensions of these effects on all economic sectors, where the issue of the Corona virus is the talk of the world now, and the concern of the governments and policies of the countries of the world, because of the consequences that resulted in changes in international economic policies, and we explain this through the following elements: (Dimensions of the Corona virus crisis on International economic sectors - Dimensions of the Coronavirus crisis on global financial markets - Dimensions of the Coronavirus crisis on the global oil crisis - Dimensions of the Coronavirus crisis on food security).